Effects of physical activity on the cardiovascular system - Tomasz Gańko; Weronika Szafrańska; Weronika Kahan; Dominika Poborowska; Marta Wojaczek; Emilia Bąk; Jacek Fordymacki; Katarzyna Polańska; Oliwia Najjar (Nicolaus Copernicus University in Toruń, 2024)
Introduction: It has been known for years that physical activity has a significant impact on human health and function. It is also inextricably linked to the cardiovascular system. It induces a number of positive changes in the cardiovascular system, both in the short term and in the long term. However, cardiovascular disease is the leading cause of death in Poland and patients affected by it constitute a very large group. In addition to appropriate pharmacotherapy, appropriately selected training and physical activity, the load and intensity of which will be planned individually for each patient, is also important. Aim of the study: The aim was to show how cardiovascular function changes during physical activity and what type of physical activity would be most appropriate in patients with cardiovascular disease. Materials and methods: The review is based on an analysis of scientific papers and materials collected from Pumbed, Google Scholar and other scientific articles using the keywords: physical activity, physical exertion, cardiovascular disease, training, cardiovascular primary and secondary prevention Conclusions: A number of changes in cardiovascular function occur during physical activity. Changes include: heart rate, blood pressure, stroke volume, cardiac output, arterio-venous difference and blood flow redistribution. By knowing how the above parameters change, we are able to offer patients with cardiovascular disease training at an appropriate frequency, intensity or load. With such tailored training, patients will be able to improve their physical parameters safely and without any concerns.